APOE ε4 alters associations between docosahexaenoic acid and preclinical markers of Alzheimer's disease. Issue 2 (11th May 2021) - Coughlan, Gillian; Larsen, Ryan; Kim, Min; White, David; Gillings, Rachel; Irvine, Michael; Scholey, Andrew; Cohen, Neal; Legido-Quigley, Cristina; Hornberger, Michael; Minihane, Anne-Marie
Abstract: Docosahexaenoic acid is the main long-chain omega-3 polyunsaturated fatty acids in the brain and accounts for 30−40% of fatty acids in the grey matter of the human cortex. Although the influence of docosahexaenoic acid on memory function is widely researched, its association with brain volumes is under investigated and its association with spatial navigation is virtually unknown. This is despite the fact that spatial navigation deficits are a new cognitive fingerprint for symptomatic and asymptomatic Alzheimer's disease. We investigated the cross-sectional relationship between docosahexaenoic acid levels and the major structural and cognitive markers of preclinical Alzheimer's disease, namely hippocampal volume, entorhinal volume and spatial navigation ability. Fifty-three cognitively normal adults underwent volumetric magnetic resonance imaging, measurements of serum docosahexaenoic acid (DHA, including lysophosphatidylcholine DHA) and APOE ε4 genotyping. Relative regional brain volumes were calculated and linear regression models were fitted to examine DHA associations with brain volume. APOE genotype modulated serum DHA associations with entorhinal cortex volume and hippocampal volume. Linear models showed that greater serum DHA was associated with increased entorhinal cortex volume, but not hippocampal volume, in non APOΕ ε4 carriers. APOE also interacted with serum lysophosphatidylcholine DHA to predict hippocampal volume. After testing interactions between DHA and APOE on brain volume, we investigated whether DHA and APOE interact to predict spatial navigation performance on a novel virtual reality diagnostic test for Alzheimer's disease in an independent population of APOE genotyped adults ( n = 46). APOE genotype modulated DHA associations with spatial navigation performance, showing that DHA was inversely associated with path integration in APOE ε4 carriers only. This exploratory analysis suggests that interventions aiming to increase DHA blood levels to protect against cognitive decline should consider APOE ε4 carrier status. Future work should focus on replicating our initial findings and establishing whether a specific dose of supplementary DHA, at a particular time in the preclinical disease course can have a positive impact on Alzheimer's disease progression in APOE ε4 carriers. Abstract : Docosahexaenoic acid's neuroprotective effect may be concentrated in the entorhinal cortex and hippocampus. Here, we show that docosahexaenoic acid's association with entorhinal volume and spatial navigation ability is modulated by the APOE genotype, with non-significant or inverse associations found in APOE ε4 carriers who are genetically-at-risk of Alzheimer's disease. Graphical Abstract: